HIGHER BURDEN OF DEPRESSION AMONG OLDER WOMEN: THE EFFECT OF ONSET, PERSISTENCE AND MORTALITY OVER TIME - Barry, Lisa C. (2008)
CONTEXT: The prevalence of depression is disproportionately higher in older women than men, yet the reasons for this gender difference are not clear. OBJECTIVE: We sought to determine whether the higher burden of depression among older women than men might be attributable to gender differences in the onset, i.e., first or recurrent episodes, or persistence of depression and/or to differential mortality among those who are depressed. DESIGN: Prospective cohort study. SETTING: General community in greater New Haven, Connecticut from March 1998 to August 2005. PARTICIPANTS: 754 persons, aged 70 years or older, who were evaluated at 18-month intervals for 72 months. MAIN OUTCOME MEASURES: The three outcome states were depressed, non-depressed and death, with scores ≥20 and <20 on the Centers for Epidemiologic Studies-Depression scale denoting depressed and non-depressed, respectively. The association between gender and the likelihood of six possible transitions, namely from non-depressed or depressed to non-depressed, depressed, or death was evaluated over time. RESULTS: The prevalence of depression was substantially higher among women than men at each of the five time points (p<0.001). In most cases, transitions between the non-depressed and depressed states were characterized by moderate to very large absolute changes in depression scores, i.e., at least 10 points. Adjusting for other demographic characteristics, women had a higher likelihood of transitioning from non-depressed to depressed (odds ratio=2.02; 95% Confidence Interval 1.39, 2.94) and lower likelihood of transitioning from depressed to non-depressed (odds ratio=0.27; 95% confidence interval 0.13, 0.56) or death (odds ratio=0.24; 95% confidence interval 0.09–0.60). CONCLUSIONS: Among older persons, the higher burden of depression in women than men appears to be attributable to a greater susceptibility to depression and, once depressed, to more persistent depression and a lower probability of death.